Executive Summary of IPITA-TTS Opinion Leaders Report on the Future of β-Cell Replacement. Issue 7 (July 2016) - Markmann, James F.; Bartlett, Stephen T.; Johnson, Paul; Korsgren, Olle; Hering, Bernhard J.; Scharp, David; Kay, Thomas W. H.; Bromberg, Jonathan; Odorico, Jon S.; Weir, Gordon C.; Bridges, Nancy; Kandaswamy, Raja; et al.
Abstract : Summary: The International Pancreas and Islet Transplant Association (IPITA), in conjunction with the Transplantation Society (TTS), convened a workshop to consider the future of pancreas and islet transplantation in the context of potential competing technologies that are under development, including the artificial pancreas, transplantation tolerance, xenotransplantation, encapsulation, stem cell derived beta cells, beta cell proliferation, and endogenous regeneration. Separate workgroups for each topic and then the collective group reviewed the state of the art, hurdles to application, and proposed research agenda for each therapy that would allow widespread application. Herein we present the executive summary of this workshop that focuses on obstacles to application and the research agenda to overcome them; the full length article with detailed background for each topic is published as an online supplement to Transplantation . Abstract : The future of β cell replacement has been considered by a global group of research and clinical leaders in the field, providing both prediction and a blueprint for the treatment of diabetes by transplantation.